Study of the Genetic Architecture in Radish - Esho, Kamal Benyamin (Edelweiss Applied Science and Technology, 2021)
The studied was to investigate for studying the genetic architecture in seven genotypes of radish during growing season autumn 2019/2020, at the area of the vegetable research, Department of Horticulture and landscape Designs, agriculture and forestry College, University of Mosul. The results indicated that highly significant variation among all the fifteen traits, vegetative, root and seeds parameters. The genotype Istanbul was superior than all genotypes for whole plant weight, root diameter and root length, number of leaves for each plant, while genotype, while Radish Shahry gave a higher value in fruit length (siliqua), genotype Black radish was superior than all genotypes for root total yield per area and total seed yields for each plant. In addition, the highest phenotypic, genotypic coefficient related to variation has been identified for the characteristics of whole plant gram weight, total chlorophyll content SPAD, root weight, total seed yield for each unit area and the number of fruits (siliqua) for each one of the plants. Almost all the characteristics showed high heritability broad sense ranging between 66.507 and 97.109%, high genetic advance as mean’s percent was indicated regarding all the traits excepted for the leaf’s number plant and seeds weight/plant. Which were 13.846, 8.769% respectively.